2009
DOI: 10.1007/s00464-008-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of medication after laparoscopic antireflux surgery

Abstract: LARS significantly reduced medication use at 1-year follow-up. However, these effects might be attributed, in part, to the multidisciplinary follow-up care. Further studies are therefore required to investigate which patients may benefit from multidisciplinary follow-up care and whether its selective application may reduce the need for medication after LARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
1
14
0
1
Order By: Relevance
“…This is cardiac mucosa with goblet cells [4] and means an increased risk for the development of esophageal adenocarcinoma (0.5% annual risk). As shown by Ciovica et al [1], antireflux surgery worked by increasing the abdominal length of the lower esophageal sphincter by approximately 1 cm, which lead to normalization of esophageal acid exposure. Recent studies showed that effective fundoplication, i.e., pH monitoring proven control of reflux, will eliminate the risk for progression toward dysplasia and cancer [5].…”
Section: Dear Editormentioning
confidence: 95%
See 3 more Smart Citations
“…This is cardiac mucosa with goblet cells [4] and means an increased risk for the development of esophageal adenocarcinoma (0.5% annual risk). As shown by Ciovica et al [1], antireflux surgery worked by increasing the abdominal length of the lower esophageal sphincter by approximately 1 cm, which lead to normalization of esophageal acid exposure. Recent studies showed that effective fundoplication, i.e., pH monitoring proven control of reflux, will eliminate the risk for progression toward dysplasia and cancer [5].…”
Section: Dear Editormentioning
confidence: 95%
“…In addition, the data by Ciovica et al [1] are of major oncological impact. Before the operation, 26.4% of patients had Barrett's esophagus.…”
Section: Dear Editormentioning
confidence: 97%
See 2 more Smart Citations
“…We read with great interest the article entitled, ''The Use of Medication after Laparoscopic Antireflux Surgery'' [1]. We congratulate the authors for their results and great efforts; however, we have the following points that we think are complementary to the educational value of the study:…”
Section: Dear Sirmentioning
confidence: 99%